Sarcoidosis as a cause of chronic back pain: a case report: Sarcoidosis and Back Pain - El Hasbani, Georges; Nicolas, Jessica; Najjar, Vicky; Jawad, Ali; Uthman, Imad (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
While sarcoidosis is typically a multisystem disease, it can, in some instances, exclusively affect the vertebrae, leading to back pain. Additionally, sarcoidosis may manifest with inflammation of the sacroiliac joints, not meeting the criteria for spondyloarthritis, yet contributing to back pain. In this report, we present a case involving a previously healthy 55-year-old woman who sought medical attention due to chronic back pain. She was subsequently diagnosed with spinal sarcoidosis, based on MRI, PET scan, and biopsy results. Furthermore, treatment with prednisolone monotherapy demonstrated substantial improvement in her symptoms.